2024
DOI: 10.3389/fendo.2023.1333826
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating early-stage diabetic retinopathy with subjective and objective perimetry

Faran Sabeti,
Joshua P. van Kleef,
Rakesh M. Iyer
et al.

Abstract: IntroductionTo prevent progression of early-stage diabetic retinopathy, we need functional tests that can distinguish multiple levels of neural damage before classical vasculopathy. To that end, we compared multifocal pupillographic objective perimetry (mfPOP), and two types of subjective automated perimetry (SAP), in persons with type 2 diabetes (PwT2D) with either no retinopathy (noDR) or mild to-moderate non-proliferative retinopathy (mmDR).MethodsBoth eyes were assessed by two mfPOP test methods that prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It identifies regional functional progression and recovery in T2D mild DR and DMO [121], including in children with type 1 diabetes (T1D) [122,123]. It has recently been shown to have superior diagnostic power compared to SITA_SWAP or Matrix 24-2 perimetry [124]. OFA is sensitive in detecting age-related macular degeneration (AMD) [119,125,126], multiple sclerosis [127], and epilepsy [128].…”
Section: Multifocal Pupillographic Objective Perimetry (Mfpop)mentioning
confidence: 99%
“…It identifies regional functional progression and recovery in T2D mild DR and DMO [121], including in children with type 1 diabetes (T1D) [122,123]. It has recently been shown to have superior diagnostic power compared to SITA_SWAP or Matrix 24-2 perimetry [124]. OFA is sensitive in detecting age-related macular degeneration (AMD) [119,125,126], multiple sclerosis [127], and epilepsy [128].…”
Section: Multifocal Pupillographic Objective Perimetry (Mfpop)mentioning
confidence: 99%
“…This response can help track retinal dysfunction in diabetic patients, potentially reflecting the severity of underlying blood vessel damage in the retina [32,106,107]. Compared with subjective automated perimetry (SAP), Sabeti et al found significant differences between the non-proliferative diabetic retinopathy for ObjectiveFIELD Analyzer (OFA; Konan Medical USA, Irvine, CA) mean defects (MDs) and pattern standard deviations (PSDs), but not for SAP MDs or PSDs [108].…”
Section: Multifocal Pupillographic Objective Perimetrymentioning
confidence: 99%